Development of Islamic banks' brand personality (IBBP) model: a conceptual study in Malaysia. Issue 3 (28th June 2019) - Ahmed, Muhammad; Ali, Syed Ahmad; Jan, Muhammad Tahir; Hassan, Arif
Abstract : Purpose: Organizations today strive to differentiate themselves from others with the help of various tools. Aaker's brand personality model is one of them. It comprises five components namely, sincerity, excitement, sophistication, competence and ruggedness. This model has been tested and supported by various scholars in the past. Similarly, it also attracted a lot of criticism especially in terms of generalizability across countries and cultures. The purpose of this paper is twofold: first, to study Aaker's model from an Islamic perspective; second, considering the dearth of brand personality knowledge in the services sector, to develop Islamic Banks' Brand Personality (IBBP) model. Design/methodology/approach: To propose IBBP model, traits in Aaker's model have been investigated in the light of selected Quranic verses and sayings of Prophet Muhammad (ahadith). Later on, content validation was conducted as a pilot study with experts from the relevant fields. Findings: Findings exhibit that Quran and hadith clearly elaborate and support majority dimensions of the existing model. Importantly, three new dimensions, namely, trustworthiness, justice and Shariah compliance, were added to develop a comprehensive IBBP model. Once the dimensions of IBBP model were finalized, the underlying items were content validated from 12 experts. Most of the items were approved; some were recommended for amendments and a few items were eliminated. Practical implications: This research contributes to the branding as well as bank marketing literature as it is the first Islamic banks' brand personality framework. With the help of IBBP model, Islamic banks can create a better brand image, use advertising strategies effectively and ultimately retain existing and attract more potential customers. Social implications: This research elaborates the personality traits of Muslim consumer market. Following IBBP model, financial needs of Muslim consumer market can be catered effectively. Originality/value: The IBBP model being first of its kind is significant for Islamic banking industry as it reflects dimensions that are supported by the Quran and hadith, and therefore suits Muslim customer market.